Destruction of bibliographic and documentary heritage in the context of the Ukrainian-Russian War (Ágora de Heterodoxias, 2024)
This research article analyzes the destruction of documentary heritage amid armed conflicts, focusing on the case of the Russian invasion of Ukraine. Firstly, context is provided on the relevance of this topic by presenting real cases that illustrate the destruction of archives during armed conflicts. The reasons behind this destruction and its negative impact on heritage and culture are analyzed. Subsequently, the methodology was constructed from a qualitative approach, opting for a descriptive-analytical investigation, with documentary research as the method and content analysis as the technique, supported by an analysis matrix as the instrument. This allowed for the establishment of a geographical and chronological reconstruction of the combats and the type of documentation seized or destroyed; identifying negative impacts such as investigative interference, anonymity of war victims, obstruction in governmental decision-making, or deprivation of historical and cultural memory; thus highlighting the consequences that this destruction represents for the patrimonial, documentary, and identity memory of the Ukrainian people.
Keywords: information sciences; international conflict; war damage to cultural property; documentary heritage; Russia and Ukraine